1998
DOI: 10.1007/bf02783969
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hair for measurement of elements by inductively coupled plasma-mass spectrometry (ICP-MS)

Abstract: The preparation of hair for the determination of elements is a critical component of the analysis procedure. Open-beaker, closed-vessel microwave, and flowthrough microwave digestion are methods that have been used for sample preparation and are discussed. A new digestion method for use with inductively coupled plasma-mass spectrometry (ICP-MS) has been developed. The method uses 0.2 g of hair and 3 mL of concentrated nitric acid in an atmospheric pressure-low-temperature microwave digestion (APLTMD) system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 16 publications
1
49
0
1
Order By: Relevance
“…Therefore the levels of some trace elements are related to animal systemic levels. Various specimens, such as blood [5][6][7]13] or hair [2][3][4]9], may be used to assess the trace element status in man and animals. The concentrations of trace elements are higher in hair than in other body organs and fluids, and sampling and storage of hair are easier than those of other biological materials [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the levels of some trace elements are related to animal systemic levels. Various specimens, such as blood [5][6][7]13] or hair [2][3][4]9], may be used to assess the trace element status in man and animals. The concentrations of trace elements are higher in hair than in other body organs and fluids, and sampling and storage of hair are easier than those of other biological materials [4].…”
mentioning
confidence: 99%
“…Hair specimens collected were a total 1.0 g of mane hair from the nape area nearest to the skin. The hair specimens were further cut and washed by the modified methods of the International Atomic Energy Agency (IAEA) [2,3,9]. The hair was first cut into 0.3 cm pieces and mixed to allow a representative subsampling of the hair specimen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three-centimeter hair specimens, including the roots, were taken from the occipital scalp of the subjects using stainless steel scissors, and 100 mg of each specimen were measured. The hair was washed using a modified method described elsewhere (Puchyr et al 1998;Yasuda et al 2005). First, the hair was washed with acetone, then with 0.01% Triton-X 100 (ICN Biomedicals, Costa Mesa, CA, USA), and finally with ultrapure water (> 18 MΩ/cm, Milli-Q water; Millipore, Bedford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…68 However, limited reports confirm that detection of Se by ICP-MS in biological samples such as hair, bone, brain, heart, liver, serum, plasma, and muscle is possible with detection limits as low as 0.09 g/liter in serum and 0.8 g/g in hair. 6,[21][22][23]31,37,49,58 A number of Se method comparison studies have been reported including measuring serum Se by HG-AAS and GFAAS, 53 analysis of dietary supplements by ETAAS and HG-AAS, 71 analysis of foods such as eggs, bread, milk, and bovine liver by ETAAS and HG-AAS, 48 and comparison of FL with HG-AAS, flow injection AAS, and HG with molecular emission cavity detection for determination of Se in standard reference materials (SRM) of bovine liver and albacore tuna. 7 To the authors' knowledge, no study has been reported that directly compares HG-AAS and ICP-MS for the detection of Se in tissues.…”
Section: Introductionmentioning
confidence: 99%